Experimental investigation on flexure and impact properties of injection molded polypropylene-nylon 6-glass fiber polymer composites - Nuruzzaman, D. M.; Kusaseh, N.; Chowdhury, M. A.; Rahman, N. A. N. A.; Oumer, A. N.; Fatchurrohman, Nanang; Iqbal, A. K. M. A.; N. M., Ismail (2018)
In this research study, glass fiber (GF) reinforced polypropylene (PP)-nylon 6 (PA6) polymer blend composites were prepared using injection molding process. Specimens of four different compositions such as 80%PP+20%PA6, 80%PP+18%PA6+2%GF, 80%PP+16%PA6+4%GF and 80%PP+14%PA6+6%GF were prepared. In the injection molding process, suitable process parameters were selected depending on the type of composite specimen in producing defects free dog bone shaped specimens. Flexure and impact tests were carried out according to ASTM standard. The important flexure properties such as flexural modulus, flexural yield strength, flexural strength and flexural strain were investigated. The obtained results revealed that flexural modulus of 80%PP+20%PA6 polymer blend is the lowest and the polymer blend composite shows steadily improved modulus as the glass fiber content is increased. Results also showed that flexural strength of pure polymer blend is the lowest but it improves gradually when the glass fiber content is increased. Impact test results revealed that impact strength of 80%PP+20%PA6 polymer blend is the highest whereas all the composites show reduced impact strength or toughness. It is noticed that 80%PP+14%PA6+6%GF composite exhibits the lowest impact strength.